Uno scritto postumo di Uberto Scarpelli sui fini e valori dell’università e sull’autonomia universitaria, e due introduzioni ai corsi di lezione (Stato, Chiese e pluralismo confessionale, 2017)
I materiali del Prof. Uberto Scarpelli sono qui pubblicati per cortesia della FamigliaSOMMARIO: I. Nota introduttiva di Silvia Zorzetto – 1. “Fini e valori dell’università e autonomia universitaria. Introduzione a studi sull’ordinamento e sullo sviluppo dell’Università di Pavia” – 2. Corso di Filosofia Morale “Logica, linguaggio e politica” – 3. Corso di Filosofia del diritto “Le scienze giuridiche e la loro funzione civile”. The aims and values of the University and the university’s autonomyABSTRACT: The entry includes three papers still unpublished written by Uberto Scarpelli in the early 1970s. As a professor of the University of Pavia he was appointed by the Chancellor to prepare a new plan of studies. In particular, the first paper is an essay upon the situation of the Italian universities in that period and a critical analysis of the concept of university’s autonomy and the role of such institution in contemporary societies. The secondand the third papers contain the programs of the courses of Moral Philosophy and of Philosophy of Law held by Scarpelli in the academic year 1970-1971. The whole is introduced by a brief note of Silvia Zorzetto that explains the relevance today of the ideas and the method of Scarpelli.